(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This article examines the American novelist Ernest Hemingway’s attempt to disrupt the dichotomy between men and women in his war novel A Farewell to Arms (1929). The article explains that Hemingway creates parallelism (similarities) between the narrator Fredric Henry and his partner Catherine Barkley. Hemingway manages to show this parallelism through revealing his major male and female characters within the context of World War I (WWI). The article focuses on the psychological as well as the physical impact of war on non-combatant civilians (the ambulance driver Fredric and the nurse Catherine). It also places A Farewell to Arms within its historical context (the Great War and its trauma), and its modernist period. It argues that Hemingway’s novel presents in a simple style some realities about WWI by which men and women appear to be similarly victimised by the war. Although accounts of the novel often highlight the centrality of problematic femininity and masculinity in the novel, critics have not fully investigated the fact that the novel creates correspondence between a man and a woman. Throughout analysing the similarities between the two characters, the paper concludes that Hemingway, a modernist who is neither a misogynist nor a feminist, attempts to release male and female characters from gendered restrictions by rejecting the stereotypical image about the dichotomy between men and women.